Metabolic and Bariatric Surgery - a Review of Available Surgical Procedures - Dworak, Kinga; Trędota , Natalia; Czyżewicz , Zuzanna; Chobot , Barbara; Wachowska , Marta; Chmielowiec , Julia; Chludek, Aleksandra; Dańda , Karol; Posid , Dominika; Lewczuk , Michał (Quality in Sport, 2026)
Introduction: The aim of this review is to provide an overview of currently available bariatric and metabolic surgical procedures. Obesity has become a global health problem, significantly increasing the risk of cardiovascular disease, type 2 diabetes, malignancies, and other chronic conditions. In patients with severe obesity, conservative treatment often fails to achieve sustained weight loss. Bariatric surgery represents the most effective therapeutic option, offering durable weight reduction and improvement of obesity-related comorbidities. Currently, sleeve gastrectomy and Roux-en-Y gastric bypass are the most commonly performed procedures, while other established and emerging techniques differ in efficacy, risk profile, and level of supporting evidence. Aim: The purpose of this review is to present a comprehensive overview of metabolic and bariatric surgical methods used in the treatment of obesity. It outlines patient qualification criteria and reviews both established procedures with proven long-term efficacy and newer surgical and endoscopic techniques with limited follow-up data. Materials and methods: A comprehensive review of the literature was conducted using the PubMed and Google Scholar databases using keywords: “obesity”, “bariatric surgery”, “weight loss surgery”, metabolic and bariatric surgery”, “obesity treatment”. References cited in the included articles were also screened to identify additional relevant sources. Conclusion: Bariatric and metabolic surgery remains a key component in the management of severe obesity. Given the diversity of available procedures, surgical strategy should be individualized based on patient characteristics and treatment goals. Further long-term studies are needed to better define the role of newer techniques and optimize outcomes in bariatric surgery.